Lyrik und Erkenntnis - Rüdiger Zymner (Universität Trier, 2019)
This text examines various positions and opinions on the question of the relationship between lyric and knowledge. In this respect, we can, on the one hand, determine traditional positions which contend that poetry may be understood as a tool of thought or at least offer access to knowledge. On the other hand, there are positions that strongly advocate the view that knowledge depends on methodically secured insight (cognition) that cannot be realized in poetry. This article adopts Gabriel’s (2013) mediating position, which assumes that there are other forms of non-propositional knowledge besides propositional knowledge, such as ‘knowingwhat-it-is-like’ and others. Following the definition of lyric by Zymner (2009), the focus is then set on the issue of how lyric may convey nonpropositional knowledge. An analysis of a poem by Herta Müller will provide an example for an imparting of lyrical knowledge by showing (‚Aufweisen‘).